Backend Infrastructure and Specifications Design Using OpenAPI and API-First on CV Elang Java Mandiri - Yohanes Bagas Ari Widatama; Nizirwan Anwar; Agung Mulyo Widodo; Arief Ichwani (Jurnal Indonesia Sosial Teknologi, 2024)
Digital transformation brings changes to the business world by increasing efficiency, convenience, security, certainty and operational speed. CV Elang Java Mandiri experienced the positive impact of this by creating software to increase operational efficiency. However, the use of direct communication between the desktop application and the database causes vulnerabilities. The lack of a bridge between the desktop application and the database also indicates a lack of flexibility when adding other applications. Ransomware attacks on desktop applications cause losses and limitations in development. This research focuses on backend updates that use API as an integrator with the API-First method. OpenAPI standards and OWASP security principles are used to increase resilience against security threats. These steps were tested with OWASP ZAP and http test. The goal is to provide solutions to company problems, meet the need for more secure applications, and make application development easier.